+0  
 
0
77
3
avatar

Find the greatest $a$ such that $\frac{7\sqrt{(2a)^2+(1)^2}-4a^2-1}{\sqrt{1+4a^2}+3}=2$.

Guest Sep 9, 2018
 #1
avatar
0

Solve for a:
5 sqrt(4 a^2 + 1) = 4 a^2 + 7

Raise both sides to the power of two:
25 (4 a^2 + 1) = (4 a^2 + 7)^2

Expand out terms of the left hand side:
100 a^2 + 25 = (4 a^2 + 7)^2

Expand out terms of the right hand side:
100 a^2 + 25 = 16 a^4 + 56 a^2 + 49

Subtract 16 a^4 + 56 a^2 + 49 from both sides:
-16 a^4 + 44 a^2 - 24 = 0

Substitute x = a^2:
-16 x^2 + 44 x - 24 = 0

The left hand side factors into a product with three terms:
-4 (x - 2) (4 x - 3) = 0

Divide both sides by -4:
(x - 2) (4 x - 3) = 0

Split into two equations:
x - 2 = 0 or 4 x - 3 = 0

Add 2 to both sides:
x = 2 or 4 x - 3 = 0

Substitute back for x = a^2:
a^2 = 2 or 4 x - 3 = 0

Take the square root of both sides:
a = sqrt(2) or a = -sqrt(2) or 4 x - 3 = 0

Add 3 to both sides:
a = sqrt(2) or a = -sqrt(2) or 4 x = 3

Divide both sides by 4:
a = sqrt(2) or a = -sqrt(2) or x = 3/4

Substitute back for x = a^2:
a = sqrt(2) or a = -sqrt(2) or a^2 = 3/4

Take the square root of both sides:
a = sqrt(2) is the largest value that satisfies the equation.
a = sqrt(2)    or    a = -sqrt(2)    or    a = sqrt(3)/2    or    a = -sqrt(3)/2

Guest Sep 9, 2018
edited by Guest  Sep 9, 2018
 #2
avatar+7336 
0

\(\frac{7\sqrt{(2a)^2+(1)^2}-4a^2-1}{\sqrt{1+4a^2}+3}\,=\,2 \)

 

 

Multiply both sides of the equation by   \(\sqrt{1+4a^2}+3\)   and note that  \(\sqrt{1+4a^2}+3\neq0\\~\\ \sqrt{1+4a^2}\neq-3\)

But there isn't a value of  a  that makes that true.

 

\(7\sqrt{(2a)^2+(1)^2}-4a^2-1\,=2(\sqrt{1+4a^2}+3)\\~\\ 7\sqrt{4a^2+1}-4a^2-1\,=\,2\sqrt{1+4a^2}+6\\~\\ 7\sqrt{4a^2+1}\,=\,2\sqrt{4a^2+1}+7+4a^2\\~\\ 7\sqrt{4a^2+1}-2\sqrt{4a^2+1}\,=\,7+4a^2\\~\\ 5\sqrt{4a^2+1}\,=\,7+4a^2\\~\\ (5\sqrt{4a^2+1})^2\,=\,(7+4a^2)^2\\~\\ 25(4a^2+1)\,=\,(7+4a^2)(7+4a^2)\\~\\ 100a^2+25\,=\,49+56a^2+16a^4\\~\\ -16a^4+44a^2-24\,=\,0\\~\\ -16(a^2)^2+44(a^2)-24\,=\,0\)

 

Let  a2  =  u  , and let's substitute   u  in for  a2 .

 

\(-16u^2+44u-24\,=\,0\\~\\ -4u^2+11u-6\,=\,0\\~\\ -4u^2+8u+3u-6\,=\,0\\~\\ -4u(u-2)+3(u-2)\,=\,0\\~\\ (u-2)(-4u+3)\,=\,0\\~\\ u-2=0\qquad\text{or}\qquad-4u+3=0\\~\\ \phantom{--}u=2\qquad\text{or}\qquad u=\frac34\)

 

Now substitute  a2  back in for  u .

 

\(\begin{array}{ccc} a^2=2&\qquad\text{or}\qquad&a^2=\frac34\\~\\ a=\pm\sqrt2&\qquad\text{or}\qquad&a=\pm\sqrt{\frac34}\\~\\ &&a=\pm\frac{\sqrt3}{2}\\~\\ a=\sqrt2\qquad\text{or}\qquad a=-\sqrt2&\text{or}&a=\frac{\sqrt3}{2}\qquad\text{or}\qquad a=-\frac{\sqrt3}{2} \end{array}\)

 

 

The greatest value of  a  that satisfies the equation is  \(\sqrt2\)  .

hectictar  Sep 9, 2018
edited by hectictar  Sep 9, 2018
edited by hectictar  Sep 9, 2018
 #3
avatar
0

a=sqrt(2)

5 sqrt(4 a^2 + 1) = 4 a^2 + 7    sub sqrt(2) for a:

5 sqrt(4sqrt(2)^2 +1) = 4sqrt(2)^2 + 7

5sqrt(4*2  + 1) = 4 * 2 + 7

5 * 3  = 8 + 7

15  =  15

So, the sqrt(2) is the largest "a" that satisfies the equation.

Guest Sep 9, 2018

25 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.